Karakteristik Fisikokimia Sosis Udang Vaname dengan Penggunaan Konsentrat Protein Kacang Kenari (Canarium indicum L.) Sebagai Emulsifier dan Binder Pati Tapioka - Nurul Putri Mariska; Rizky Muliani Dwi Ujianti; Fafa Nurdyansyah; Arief Rakhman Affandi (Universitas Mataram, 2026)
This study aimed to evaluate the effect of adding walnut protein concentrate as a natural emulsifier on the functional and physicochemical characteristics of whiteleg shrimp sausage. The parameters analyzed included moisture content, fat content, water-holding capacity (WHC), protein content, emulsion stability, and texture (hardness, cohesiveness, and springiness). The research employed a factorial randomized block design (RBD) with two factors: the concentration of walnut protein concentrate (2%, 3%, and 4%) and the concentration of tapioca starch binder (3% and 4%). The results showed that adding walnut protein concentrate and tapioca starch significantly influenced all tested parameters. The moisture content ranged from 75.05% to 76.56%, fat content from 1.27% to 1.77%, WHC from 83.42% to 93.09%, protein content from 12.41% to 12.65%, emulsion stability from 82.67% to 86.67%, and hardness from 11.42 N to 18.65 N Cohesiveness was 0.7, and springiness was 0.9. The best treatment was found in the combination of 4% walnut protein concentrate and 3%–4% tapioca binder, depending on the parameter measured. The 4% concentrate and 4% binder combination yielded the highest moisture, fat content, and WHC, while the 4% concentrate and 3% binder combination produced the best emulsion stability and protein content. These findings suggest that walnut protein concentrate has strong potential as an effective plant-based emulsifier in shrimp-based sausage products.